G73(P) The Prevalence of Paediatric-onset Inflammatory Bowel Disease: A Systematic Review. (7th April 2014) - Cameron, FL; Henderson, P; Wilson, DC
Abstract : Background: Previous systematic reviews demonstrated the worldwide increase in incidence of adult and paediatric-onset IBD (PIBD), however, little is known about PIBD prevalence. Disease prevalence is crucial to inform effective service provision and delivery. We aimed to assess the evidence on worldwide prevalence of PIBD, geographic distribution and trend analysis using systematic review. Methods: A literature search was performed using MEDLINE (1950–2012), Medline in progress, Cochrane database and EMBASE (1980–2012) to identify relevant population-based studies. Included studies reported distinct paediatric prevalence, total Inflammatory Bowel Disease (IBD), Crohn's disease (CD), Ulcerative colitis (UC), Inflammatory Bowel Disease Unclasssified (IBDU) or any combination of these. Abstracts in all languages were considered but only included if full text was available. Data was extracted on source of prevalence data, age ranges, country of origin, diagnostic criteria and methodology. Results: 4190 references were reviewed; 27 studies which presented data on the prevalence of PIBD and/or CD and/or UC from 11 countries were included. No prevalence data were presented on IBDU. The prevalence of PIBD ranged from 6.0–30.0 per 100, 000 while CD ranged from 0.5–85.3 per 100, 000 and UC from 3.0–90.1 per 100, 000. Two studies provided trend analysis over time, showing an increasing PIBD prevalence during a 5 and 10-year period respectively. Most studies were from developed countries: 8 from North America, 10 from Europe, 5 from the Middle East, 2 from Asia, 1 from Africa, and 1 from Australasia. Prevalence rates were highest in North America and lowest in Africa and Asia. 74% were retrospective, using a variety of sources: national registries, insurance databases, retrospective case note review and physician survey. No true population-based studies were reported. Age ranges and diagnostic criteria used varied widely. Conclusions: PIBD prevalence was highest in North America and Europe with little data from developing nations and insufficient data to analyse trends over time. Data was heterogeneous in terms of diagnosis of disease, method of case accrual and age ranges making interpretation challenging. Well-designed studies with clear diagnostic criteria and age ranges will confirm if PIBD prevalence is increasing.